Application of deep learning-based diagnostic systems in screening asymptomatic COVID-19 patients among oversea returnees - Dawei Dong; Zujin Luo; Yue Zheng; Ying Liang; Pengfei Zhao; Linlin Feng; Dawei Wang; Ying Cao; Zhenhao Zhao; Yingmin Ma (Journal of Infection in Developing Countries)
Introduction: Our study aimed to investigate the performance of deep learning (DL)-based diagnostic systems in alerting against COVID-19, especially among asymptomatic individuals coming from overseas, and to analyze the features of identified asymptomatic patients in detail.